Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.